Concentration Effect of Fluoroethylene Carbonate on Formation of Solid Electrolyte Interphase Layer in Sodium-Ion Batteries - Bouibes, Amine; Takenaka, Norio; Fujie, Takuya; Kubota, Kei; Komaba, Shinichi; Nagaoka, Masataka (ACS applied materials & interfaces, 2018)
Fluoroethylene carbonate (FEC) is an effective additive to improve the performance of Na-ion batteries (NIB). Recent experimental study showed that a small amount of FEC enhances the NIB performance, while it deteriorates by increasing the FEC amount. Toward understanding the microscopic mechanism of this observation, the dependency of the solid electrolyte interphase (SEI) film formation on the FEC concentration has been investigated in propylene carbonate (PC) based electrolyte solution by using the Red Moon method. This method was able to reproduce successfully the experimental observations where a small amount of FEC makes SEI film stable. Further, the increase of FEC amounts decreased the stability of SEI film and should lead to the decrease in the NIB lifetime during charge-discharge cycles. It was microscopically revealed for the first time that this is due to the insufficient organic dimer formation between the monomer products at the higher FEC concentration. Finally, it was reconfirmed theoretically that the appropriate adjustment of FEC additive amount is essential to develop the high-performance of NIB.